Was Scotland deglaciated during the Younger Dryas?. (1st August 2016) - Small, David; Fabel, Derek
Abstract: Recent work has produced data that challenges the canonical view that the Younger Dryas (c.12.9–11.7 ka) was a time of glacier expansion across the North Atlantic. Boulders on moraines located within the inner sector of the Scottish Loch Lomond Stadial (≈Younger Dryas) ice cap yield cosmogenic exposure ages 12.8–11.3 ka with a best estimate moraine age of 11.5 ± 0.6 ka. This age contradicts the interpretation that Scotland was completely deglaciated as early as 12, 580 cal yr BP and no later than 12, 200 cal yr BP. Our data supports the previously accepted scenario, supported by a wide variety of data, that final deglaciation of Scotland did not occur until late in the Loch Lomond Stadial or the early Holocene. Highlights: New 10 Be exposure ages constrain Younger Dryas deglaciation of Scotland. Four ages cluster at 11.5 ± 0.6 ka. Suggests deglaciation occurred in the late Younger Dryas – early Holocene. Not consistent with suggestion of Early – mid Younger Dryas deglaciation.